STOCHASTIC OPTIMIZATION OF MULTIPLEX CHARGES BASED ON INTERIOR BALLISTICS SIMULATIONS - Caldeira, A. B.; Cury, T. L. B.; Rezende, A. L. T.; Gomes, A. V. (Revista de Engenharia Térmica, 2017)
Multiplex charges combine propellant grains with regressive, neutral and progressive burning behaviors in a single propellant charge to improve the interior ballistics. This work optimizes the mass and the web thickness of each type of propellant grain used in a multiplex charge. Two optimization problems are studied: the maximization of the muzzle velocity and the minimization of the maximum pressure inside the gun. Particle Swarm Optimization (PSO) and Differential Evolution (DE) were used to solve the optimization problems. The interior ballistics of a 155 mm howitzer was simulated by using a lumped parameters model. In this model, the lost energy and the resistance pressure are defined by spline functions based on reference data. The results show that optimized multiplex charges can be used to increase the weapon’s utility range and to reduce the weapon’s weight.